Pulmonary impairment by paracoccidioides (Research, Society and Development, 2023)
Paracoccidioidomycosis (PCM) is a systemic granulomatous disease that can affect any organ, especially the lungs. This article aims to review the literature on pulmonary involvement in P. brasiliensis infection, addressing pathophysiological aspects, diagnostic methods and the most appropriate therapeutic approach in these cases. This study is based on an integrated literature review, the bases used were National Library of Medicine National Institutes of Health (PubMed), Virtual Health Library (BVS/MEDLINE) and Science Direct, published from 2017 to 2022. A total of 1560 studies were identified and 4 were included in the final analysis. In the 4 articles it was possible to show that the early diagnosis of pulmonary involvement in chronic paracoccidioidomycosis brings benefits to minimize disease sequelae. All articles cited the correlation between chronic paracoccidioidomycosis and pulmonary involvement. Thus, it was possible to observe that among the benefits of early diagnosis of paracoccidioidomycosis is the decrease in pulmonary complications resulting from the disease and the decrease in mortality from the disease, as well as the reduction of hospital costs.